Chronic recurrent emesis in a geriatric patient with jejunal cavernous hemangioma misdiagnosed as diabetic gastroparesis - Li-Yan Liu; Xun Sun; Yan Zhu; Xiang-Wei Meng; Quan Wang; Yuan-Jie Sun (Turkish Journal of Gastroenterology, 2019)
-